Qur'anic style in disclosing the behavioural features of Hypocrites - Azhari, Mizanur Rahman; Osmani, Noor Mohammad (Dept of Qur'an and Sunnah, 2022)
Hypocrite is a person who acts as a pious believer, though not having faith, or is a person whose inward reality differs from outward appearance. Hypocricy is an extremely dangerous disease of Ummah that weakens a believer’s faith and damages his soul. That is why Allah (SWT) warns the true believers against hypocrisy. The Holy Qurʾān addressed hypocrisy in several verses in different styles. Form the time of the Prophet (P.B.U.H) until now, these hypocrites are being considered a great threat for Islam and Muslims. In this connection, the aim of this paper is to identify the way Qurʾān unveils the characteristics of hypocrites with different styles by using inductive as well as analytical method. Among the most significant findings of this paper is that Qurʾān did not focus on their behavioural features only rather noted their intention, thinking, statements, activities, feelings and provided some symbolic signs to disclose their behavioural feature.